Ethical Aspects concerning Instrument Separation and Perforations during Endodontic Treatment: A Cross-Sectional Study - Raidan Ba-Hattab; Ishrat Rahman; Lubna K. Elsayed; Wejdan F. Alasmari; Randa Abidia; Somayah Abdelgaffar; Awsan Bahattab (International Journal of Dentistry)
Aim. During endodontic treatment, dentists may face various unwanted procedural accidents, at any stage of the treatment that might compromise endodontic treatment outcome and bring obstacles to dentists as well. This study aimed to address and analyze several ethical concerns relating to the behavioural conduct of dentists towards endodontic instrument separation as well as perforation of the crown and/or root during root canal treatment in Riyadh, Saudi Arabia. Method. Hundred and eleven questionnaires were distributed among dentists working in Riyadh in university clinics and government and private sectors. Data were collected, reviewed, and statistically analyzed by Fisher’s exact and chi-square tests at a 5% significance level, using SPSS software. Results. 54.5% of the respondents have encountered instrument separation. 53.2% stated that they would inform the patient about the instrument separation. 43.6% of the respondents had experienced perforation during root canal treatment, and 54.9% reported that they would inform the patient of the accident. Conclusion. Within the limitation of this survey, we concluded that most of the dental professionals did not hesitate to adhere to the correct ethical conduct, and they would inform the patient if an incident occurred.